Lymphocytic thrombophilic arteritis complicated by systemic involvement. (6th April 2018) - Wee, Edmund; Nikpour, Mandana; Balta, Showan; Williams, Richard A; Kelly, Robert I
Abstract: Lymphocytic thrombophilic arteritis (LTA) is a recently described entity defined by primary lymphocytic vasculitis; it typically has a chronic indolent course. We describe a patient who presented with clinical and histological findings consistent with LTA and later developed bilateral focal testicular infarcts as well as an acute median nerve neuropathy.